Mareks Disease in Chicken: Clinico-Pathological Aspect and Diagnosis - Damayanti, Rini; Hamid, Helmy (Indonesian Bulletin of Animal and Veterinary Sciences, 2002)
Marekâs is a limphoproliferative and oncogenic disease of poultry caused by a serotype 1 herpesvirus. Â Chicken Â between 10 and 15 weeks of age are the most susceptible although in some outbreaks it also affects other ages. The causal agent consists of Â some Â virus Â strains Â with Â different Â pathotypesÂ  causing Â a Â variety Â of Â clinical Â and Â pathological manifestations. The Â main pathological features are neurological lesion and lymphoma formation in some visceral organs. Marekâs disease is clinically classified as classical, acute, peracute and chronic with neurological disorder and superficial tumor. At necropsy the peripheral nerves were enlarged, discoloured and loss of striation. There were formation of lymphoid tumour in various visceral organs. Microscopically Marekâs produced non suppurative encephalitis/neuritis and pleomorphic tumour. The diagnosis is based on the history of the disease, age of affected chicken, clinical and pathological features. A definitive diagnosis is made by virological and serological tests. Some of the Marekâs cases in Indonesia were discussed in this paper, as well as review on clinico- pathological aspects how to confirm the diagnosis of Marekâs. Â  Key words. Marekâs Disease, chicken, clinical, pathological, diagnosis